Fabrication of CuS/CuO nanowire heterostructures on copper mesh with improved visible light photocatalytic properties. (May 2020) - Wu, Chongchong; Sun, Yangang; Cui, Zhe; Song, Fengge; Wang, Jie
Abstract: CuS/CuO nanowire heterostructures grown on copper mesh (CuS/CuO/Cu) have been successfully synthesized by a liquid–solid reaction at room temperature followed by annealing. The proposed structure has been verified by X-ray diffraction analysis. Scanning electron microscopy images have indicated that the density and diameter of CuS nanoparticles on CuO nanowires can be tuned by controlling the duration of sulfonation with Na2 S. Photocatalytic studies have revealed that CuS/CuO/Cu heterostructures offer improved photocatalytic activity in the degradation of Methylene Blue (MB) in the presence of H2 O2 . A sample designated as CuS/CuO/Cu-10, where "10" denotes sulfonation with Na2 S for 10 min, showed the best photocatalytic properties, with MB degradation efficiencies under visible light irradiation of 87.4% after 20 min and 98.6% after 40 min. The enhanced photocatalytic activity can be attributed to effective electron–hole separation and improved visible light utilization due to the cooperative effect of the CuS/CuO heterostructures and conductive copper mesh. Graphical abstract: CuS/CuO nanowire heterostructures on Cu mesh have been fabricated through a two-step method of sulfonation and annealing. The formation of CuS/CuO nanowire heterostructures on Cu mesh obviously improves the visible light absorption of CuO/Cu and promotes the separation of photogenerated charge carriers. A sample designated as CuS/CuO/Cu-10 exhibited the best photocatalytic activity and stability in the degradation of Methylene Blue in the presence of H2 O2 . Image 1 Highlights: CuS/CuO/Cu nanowire heterostructures have been fabricated by a sequence of sulfonation and annealing. The formation of CuS/CuO heterostructures improves the photocatalytic activity of CuO/Cu. The amount of CuS on a CuO surface affects the catalytic activity of CuS/CuO/Cu.